The ICT Sector in Costa Rica: Economic importance, evolution, and policy considerations for its future development - Mata Chavarría, Francisco J (2025)
The information and communication technologies (ICT) sector has played a significant role in Costa Rica as part of the country’s outward-oriented development strategy, which focuses on promoting non-traditional exports and attracting foreign direct investment (FDI). The country’s geographic location has facilitated nearshoring processes within the ICT product supply chain promoted by technology companies in the United States (U.S.). Additionally, the development of human capital in the country has enabled the establishment of outsourcing operations related to ICT services. This paper emphasizes the economic importance of the ICT sector for Costa Rica and discusses the implications of the current geopolitical context —shaped by a complex geopolitical environment and the new U.S. administration— on the sector’s sustainability. The analysis is grounded in the fact that the ICT sector exhibits agglomeration characteristics that support the formation of technological clusters. Based on this analysis, policy recommendations are proposed to strengthen the sector. However, it is important to acknowledge that the current global economic environment is highly complex and uncertain, which makes it difficult to plan accordingly.